CTL-Derived Granzyme B Participates in Hippocampal Neuronal Apoptosis Induced by Cardiac Arrest and Resuscitation in Rats - Ji, Ning-Ning; Wu, Liang; Shao, Bo-Ming; Meng, Qing-Xiang; Xu, Jin-Nan; Zhu, Hao-Wen; Zhang, Yong-Mei (Frontiers in Neurology, 2019)
Hippocampal neuronal apoptosis is a devastating consequence of cardiac arrest (CA) and subsequent cardiopulmonary resuscitation (CPR). In this study, we examined the contribution of cytotoxic T lymphocyte (CTL)-derived toxic mediator Granzyme B (Gra-b) to the hippocampal neuronal apoptosis following CA/CPR in rats. Rats that experienced CA/CPA presented karyopyknosis, cell fragmentation and neuronal necrosis in the CA1 region of dorsal hippocampus. CA/CPR rats also showed impairment in spatial navigation and a local infiltration of peripheral CD8+ T cells into hippocampus. The protein levels of Gra-b, caspase-3, and PARP were significantly increased in rats that experienced CA/CPR. Gra-b inhibitor pretreatment suppressed Gra-b release, attenuated hippocampal neuronal apoptosis, and improved cognitive impairment. Together, this study indicates that CTL-derived Gra-b participates in the CA/CPR-induced neuronal apoptosis, and pharmacological manipulation of Gra-b may represent a novel avenue for the treatment of brain injury following CA/CPR.